75.1k views
4 votes
Simplify the expression

Simplify the expression-example-1

2 Answers

5 votes

Answer:

17

Explanation:


(17^{(1)/(7) })^(7) = 17^{(1)/(7) } 17^{(1)/(7) } 17^{(1)/(7) }17^{(1)/(7) }17^{(1)/(7) }17^{(1)/(7) }17^{(1)/(7) } = 17^{(1)/(7)+(1)/(7) +(1)/(7)+(1)/(7)+(1)/(7)+(1)/(7)+(1)/(7) }=17^{(7)/(7) } =17^(1) = 17

User David Conlisk
by
5.1k points
4 votes

Answer:


(17^(1/7) )^(7) =
17^(1/7 * 7 ) =
17^(1) = 17

hope this answer helps you.....

User Cory Mawhorter
by
4.2k points